Implementation of Multicultural Islamic Religious Education at SMP Negeri I Nubatukan - Salehudin Mahmud; Tobroni; M. Nurul Humaidi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research discusses the evolution and implementation of a multicultural Islamic Religious Education (PAI) framework at SMP Negeri I Nubatukan, with the aim of instilling the principles of diversity and tolerance to students. This research describes the methodologies and strategies used in the implementation of multicultural PAI pedagogy at SMP Negeri I Nubatukan, as well as describing the conceptualization of multicultural PAI, which has been designed to seamlessly incorporate the values of diversity and tolerance. This qualitative research used a qualitative approach. Data collection techniques included participatory observation, open-ended interviews, and document analysis. The data analysis methods used included thematic analysis, triangulation for data validation, and participant feedback. The findings showed that the multicultural PAI approach significantly contributed to students' character development, fostering an environment of inclusiveness, tolerance, and the ability to engage peacefully with peers from different backgrounds. It is recommended that efforts be intensified to strengthen the implementation of multicultural Islamic Religious Education (PAI) at SMP Negeri I Nubatukan, focusing on curriculum improvement, professional development for PAI educators, integration of technology and media, collaboration with community entities and other institutions, extracurricular initiatives, and systematic monitoring and evaluation.